2014
DOI: 10.1111/cas.12436
|View full text |Cite
|
Sign up to set email alerts
|

Busulfan inhibits growth of human osteosarcoma through miR‐200 family microRNAs in vitro and in vivo

Abstract: Osteosarcoma typically arises in tissues of mesenchymal origin, and is the most malignant bone tumor characterized by high local aggressiveness, with poor therapeutic outcome. Busulfan has been widely used to treat CML. So far, there are no reports on the therapeutic effect of busulfan on osteosarcoma. Here, we showed that busulfan dose-dependently reduced the cell viability and proliferation, and induced cell apoptosis, senescence, and reactive oxygen species levels in two osteosarcoma cell lines. Moreover, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 22 publications
0
55
0
2
Order By: Relevance
“…This results in mRNA degradation or inhibition of post-transcriptional translation, thereby altering processes related to the cell cycle, apoptosis, cell proliferation and cell migration (19). miRNA-130b is located on chromosome 22 and the mature sequence is 22 nucleotides in length.…”
Section: Discussionmentioning
confidence: 99%
“…This results in mRNA degradation or inhibition of post-transcriptional translation, thereby altering processes related to the cell cycle, apoptosis, cell proliferation and cell migration (19). miRNA-130b is located on chromosome 22 and the mature sequence is 22 nucleotides in length.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion miR-574 has been found to be upregulated in several types of cancers, including lung cancer, bladder cancer and prostate cancer (11)(12)(13)19). Foss et al (17) also suggested miR-574 as a serum biomarker of non-small cell lung cancer.…”
Section: Downregulation Of Mir-574-3p Inhibited Cell Growth and Inducmentioning
confidence: 93%
“…All diagnoses were based on pathological and/or cytological evidence (10). The histological features of the specimens were evaluated by senior pathologists according to the World Health Organization classification criteria (11)(12)(13). Tissues were obtained prior to chemotherapy and radiotherapy, and were immediately frozen and stored at -80˚C prior to reverse-transcription quantitative polymerase chain reaction (RT-qPCR) assay (3,5,10).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of these miRs, miR-133, has been shown to play a role in tumor suppression in a variety of cancers, including inhibiting breast cancer cell migration and invasion, gastric cancer cell growth and migration, and liver fibrosis (Esquela- Kerscher and Slack, 2006;Cheng et al, 2012;Liu et al, 2014;Mei et al, 2014;Wang et al, 2014;Yongchun et al, 2014;Xie et al, 2015;Zhang et al, 2015). Recent studies have shown that miRs may be a new regulatory mechanism involved in the onset of pituitary adenoma, providing a new method for the diagnosis and treatment of pituitary adenoma (Trivellin et al, 2012;Gadelha et al, 2013;Di Ieva et al, 2014;Leone et al, 2014).…”
Section: Introductionmentioning
confidence: 99%